Accreditation Assistance For Jurnal Teknik Elektrosista At Magelang Military Academy - Silitonga, Frangky; Nasution, M Nur; Cahayani, Kartika; Lubis, Arina Luthfini; Hifni, Muchammad; Ahsan, Ahmad Nur; Purify, Aura; Nurtjahyono, Nurtjahyono (PUSLITABMAS-Politeknik Pariwisata Batamc, 2026)
Assistance in the accreditation of scientific journals is a strategic step in improving the quality of academic publication governance, especially in the Defense Electrical Engineering Study Program at the Magelang Military Academy. Scientific journals play an important role as a medium for disseminating the research results of lecturers and cadets, as well as a means of strengthening the culture of research and scientific development in the field of defense technology. Therefore, efforts to assist journal accreditation are an urgent need so that journal management meets the national standards set by the Ministry of Education, Culture, Research, and Technology. The mentoring activities are focused on strengthening journal management based on Open Journal Systems (OJS), starting from structuring the editorial structure, preparing publication ethics policies, improving article templates, to optimizing the peer review process. In addition, the assistance also includes improving the quality of the article substance, publication consistency, completeness of metadata, and fulfilling the technical aspects of accreditation such as DOI, indexation, and citation. Through a participatory approach, the coaching team works intensively with journal managers to ensure that each stage of accreditation can be understood and implemented properly. The results of the mentoring activities showed a significant increase in journal managers' understanding of accreditation standards, improved quality of editorial governance, and the readiness of journals to participate in the national accreditation process. This assistance not only has an impact on the administrative aspect, but also encourages the professionalism of the management and the sustainability of the journal as an academic asset of the institution. With the realization of accredited journals, the Defense Electrical Engineering Study Program at the Magelang Military Academy is expected to be able to strengthen its academic reputation, support the tridharma of higher education, and contribute to the development of national defense science and technology.